A progressive Islamic movement and its response to the issues of the ummah - Zuly Qodir; Hasse Jubba; Mega Hidayati; Irwan Abdullah; Ahmad Sunawari Long (IAIN Salatiga, 2020)
This article discusses the progressive Islamic movement developed by Muhammadiyah, a modernist Islamic organization established by Ahmad Dahlan on November 18, 1918. History has shown that Muhammadiyah, as a modernist Islamic organization, has instigated various social transformations that continue to affect Indonesian society by creating schools, hospitals, and orphanages that were inspired by modern, Westernized systems and modernist interpretations of the Qur'an. Even today, Muhammadiyah remains active in national activities and discourse, continuously responding to the ever-changing times. This article departs from the argument that the progressive movement developed by Muhammadiyah was translated from Ahmad Dahlan's desire to advance the ummah and to create a just and prosperous world, one that has been blessed by God. As such, it argues that Muhammadiyah's response to the problems of its ummah has been informed by the history of the movement and its founders.